Garrison Keillor's comedy theater [compact disc] : more songs and sketches from A prairie home companion. - Keillor, Garrison (HighBridge, 1997)
Enjoy the best of Garrison Keillor's comic fables from A Prairie Home Companion, all about true love and other tribulations, brought to life by a cast of brilliant radio actors.